Reliability and validity of a standardised ultrasound examination protocol to quantify vastus lateralis muscle - Theresa Maria Betz; Michaela Wehrstein; Fabian Preisner; Martin Bendszus; Birgit Friedmann-Bette (Medical Journals Sweden, 2021)
Objective: To evaluate the reliability and validity of a standardized ultrasound examination protocol for measuring vastus lateralis muscle size. Design: Prospective cohort study. Subjects: Sixteen staff members of the university hospital of Heidelberg. Methods: Muscle thickness, cross-sectional area and subcutaneous adipose tissue thickness were measured at 3 standardized sites on the right and left vastus lateralis muscle. Ultrasound measurements were collected by 2 independent investigators on 2 different days and compared with magnetic resonance imaging measurements. Results: Intraclass correlation coefficients (ICC) for intra- and inter-rater reliability showed very good closeness of agreement for all parameters (ICC = 0.929-0.994, p < 0.001). Muscle thickness and subcutaneous adipose tissue thickness ultrasound and magnetic resonance imaging measurements revealed good to very good closeness of agreement (ICC = 0.835-0.969, p < 0.001), whereas cross-sectional area showed only average closeness of agreement (ICC = 0.727, p < 0.001). A strong predictive positive correlation for ultrasound and magnetic resonance imaging-based measurements of cross-sectional area was found (R² = 0.793, p < 0.001). Conclusion: By standardization of an examination protocol, quantitative vastus lateralis muscle ultrasound proved to be a reliable method for assessing vastus lateralis muscle size. Furthermore, this protocol is valid for measuring muscle thickness and subcutaneous adipose tissue thickness, although there seems to be a systematic underestimation of cross-sectional area depending on subcutaneous adipose tissue thickness.